CuO nanoparticles supported on silica: a simple, efficient, and recyclable catalyst for hydroacylation reactions of aldehydes with azodicarboxylate - Inamdar, Suleman M.; More, Vinod K.; Mandal, Sisir K. (Chemistry Letters, 2012)
We describe a green and efficient procedure for the hydroacylation of aldehydes with diisopropyl azodicarboxylate, using CuO nanoparticles supported on silica (CuO-np/SiO2) as a catalyst, in good to excellent yields. A wide range of aldehydes, including aromatic and aliphatic compounds, were considered. The catalyst is found to be truly heterogeneous in the reaction mixture and can be reused without loss of catalytic activity.